TRACES OF INTERFERENCE IN URBAN MUSIC LYRICS: A CASE STUDY OF LANGUAGE CONTACT IN THE SONG GARAM DAN MADU BY NAYKILLA, TENXI, AND JENSII - Riyadi, Rofiq; Salman S M, Muhammad; Armila, Meinisa (Media Inovasi Pendidikan dan Publikasi, 2025)
This study aims to analyze the lyrics of the song Garam dan Madu by Naykilla, Tenxi, and Jensii. Interference can be interpreted as the use of other language elements that are considered as an error because they deviate from the rules of the language used. In compiling it, this study uses a qualitative approach with descriptive analysis techniques to understand the context or social symptoms that occur and their impact in the social context. The results of the study found several deviations due to language contact which were then classified into four characteristics, namely: phonological, morphological, syntactic, and semantic. Each word is analyzed based on its structure and the context of its use in the song lyrics. This simple analysis shows that the use of language contact contained in the lyrics of the song Garam dan Madu by Naykilla, Tenxi, and Jensii has an important role and influence in building psychological dynamics and an atmosphere that relates to every group of listeners. This study is expected to be able to break through psycholinguistic studies and become a reference in understanding the elements of language that influence the creation of song lyrics and their impact on popular works.